Heading to provincial championship boxing 2020 east java: A study of physical condition in ontang-anting sasana boxing athletes - Zawawi, M. Anis; Firdaus, Mokhammad; Zawawi, Anis (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
The research objective was to see the physical condition of boxing athletes in the ontang-anting gym prepared for the 2020 championship, as well as to prepare for PORPROV in 2022 because the majority of athletes are included in the Kediri City PUSLATKOT team. The research method used a quantitative descriptive approach. This type of research was non-experimental. The research population was all male and female boxing athletes, male and female, 15 athletes. Sampling technique with saturated sampling. The data collection instruments were in the form of tests and measurements, while the test items included leg muscle strength, leg muscle power, arm power, arm muscle strength, leg muscle agility, cardiovascular endurance and back flexibility. Data analysis using a percentage. The results of this study show the results of the overall tests carried out, athletes who are in the very good category are 20.00%, athletes who are in the good category are 46.67%, athletes who are in the moderate category are 20. , 00%, while athletes who were in the poor category were 6.67% and those who were in the less category were 6.67%).